The effects of acute sprint exercise and the mode of Live High : Train Low on skeletal muscle Na+,K+ATPase - Aughey, R. J.; Hawley, J. A.; Clark, S. A.; Gore, C. J.; Hahn, A. A. G.; Townsend, N. E.; Chow, C.-M.; Kinsman, T. A.; Roberts, A. D.; Goodman, C. A. M.; McKenna, M. J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction The skeletal muscle Na+,K+ATPase enzyme is critical in maintaining muscle trans-sarcolemmal [Na+] and [K+] gradients, membrane excitability and thus Na+,K+ATPase activity has been linked with fatigue. Chronic hypoxia and training in hypoxia decrease Na+,K+ATPase activity. Athletes typically use Live High Train Low (LHTL) hypoxic exposure at real or simulated altitudes of up ~2700 m for up to 20 nights to improve performance. We have shown a small but significant reduction in Na+,K+ATPase activity with LHTL for 23 nights at a simulated altitude of 3000 m. The aims of our study were to examine the effects of LHTL mode and timecourse of adaptation on Na+,K+ATPase activity, content, plasma [K+] and performance. Methods We randomly assigned 33 well-trained endurance athletes to a consecutive (LHTLc, 20 n LHTL), intermittent (LHTLi, 4 x 5 n LHTL with 2 n normoxia), or control (CON) group. LHTL slept at simulated moderate altitude (2650 m) for 20 nights and lived and trained by day under normoxic conditions in Canberra (~600m); CON lived, trained and slept in normoxia. Vastus lateralis muscle samples were obtained at rest and immediately following sprint cycling exercise at 170% pre-determined peak power output both before (Pre), during (d5) and after (Post) intervention. Muscle was analysed for Na+,K+ATPase activity and content. Arterialised venous blood was sampled from a dorsal hand vein and analysed for plasma [K+]. Performance was measured from fatigue index calculated as the percentage decline in cadence during exercise. 2.3±0.2% respectively, P<0.05, Fig 1), but was unchanged in CON. Na+,K+ATPase activity (d5-Post, Fig 1) was unchanged in LHTLc and CON (-0.8±0.7% and 0.5±0.6 respectively, NS, Fig 1), but was increased in LHTLi (3.5±1.2%, P<0.05, Fig 1). The Pre - Post change in resting Na+,K+ATPase activity was lowered in LHTLc (-2.9±0.7%, P<0.05), remained unchanged in CON (0.8±1.0%), but tended to increase in LHTLi (1.1 ± 1.2%). Plasma [K+] rose with exercise and then declined post-exercise (P<0.05), but was unchanged by LHTL. Performance was increased in each group by d5, remaining high after LHTL or Con interventions. Conclusion Exercise reduces Na+,K+ATPase activity; 5 n LHTL reduces Na+,K+ATPase activity with restoration when using intermittent LHTL; and Na+,K+ATPase content is unchanged after sprint exercise or LHTL interventions Neither plasma [K+] nor performance altered with LHTL.